PERAN KEPUASAN KERJA PEMEDIASI MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DINAS TANAMAN PANGAN HORTIKULTURA DAN PERKEBUNAN KOTA SUNGAI PENUH - Sudirman .; Melifia Liantifa (LPPM - STIE SAKTI ALAM KERINCI, 2021)
This study aims to determine: the extent of the influence of work motivation on the performance of employees of the Horticultural Food Plantations and Sungai Penuh City Plantation. the influence of work motivation on job satisfaction of employees of the Horticultural Food Crops and Plantation Plants in Sungai Penuh City. the extent of the influence of the work environment on the job satisfaction of employees of the Horticultural Food and Plantation Plants City of Sungai Penuh. the extent of the influence of job satisfaction on the performance of employees of the Horticultural Food and Plantation Plants City of Sungai Penuh.The population in this study were all employees at the Horticultural Food Crops and City of Sungai Penuh Plantations, totaling 41 people. Furthermore, it was found that all populations were sampled as many as 41 respondents with saturated sampling techniques. The data analysis tool used is path analysis at an alpha level of 0.05. The result of analysis found that job satisfaction was not found as mediation variable between motivation and performance employee, job satisfaction was not found as mediation variable between work environment and performance employee.